2021
DOI: 10.3390/pathogens10010055
|View full text |Cite
|
Sign up to set email alerts
|

The Vector-Borne Zoonotic Nematode Thelazia callipaeda in the Eastern Part of Europe, with a Clinical Case Report in a Dog in Poland

Abstract: Thelazia callipaeda is a zoonotic nematode transmitted by drosophilid flies. It causes ocular thelaziosis, a disease of carnivores, such as dogs, cats, and foxes, and also humans. The parasite has thus far been observed in various areas of Eurasia, including 20 countries within Europe. The present study documents its presence in the south-east region of Poland, near the Ukraine border. An adult nematode was removed from the conjunctival sac of a dog showing ocular inflammation and purulent discharge. The dog’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The infection in carnivore hosts may vary from asymptomatic to clinical signs characterized by conjunctivitis, mucus, corneal ulcers, red eyes, blepharospasm, corneal oedema, and mucopurulent discharge ( Sargo et al, 2014 ; Papadopoulos et al, 2021 ). In addition, the presence of adult worms in the eyes causes discomfort and may expose the animals to opportunistic bacterial infections, which may have more severe consequences ( Rolbiecki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The infection in carnivore hosts may vary from asymptomatic to clinical signs characterized by conjunctivitis, mucus, corneal ulcers, red eyes, blepharospasm, corneal oedema, and mucopurulent discharge ( Sargo et al, 2014 ; Papadopoulos et al, 2021 ). In addition, the presence of adult worms in the eyes causes discomfort and may expose the animals to opportunistic bacterial infections, which may have more severe consequences ( Rolbiecki et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the patient was living and working as a farmer in a rural area and had a cat in his house, all of which may be related to this pathological finding. Several studies suggested a relationship between human ocular thelaziasis and rural settings, improper personal hygiene, low socio-economic status, and rearing livestock or parasitized animals, such as sheep, dogs, pigs, and cats, in the same environment where humans reside [ 16 , 17 , 18 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The tail of the female was straight and that of the male was ventrally curved with several pairs of papillae in front of the anus (Figure 5D). According to Rolbiecki [22,23], the worms were identified as T. callipaeda based on key morphological features. Four male and seven female T. callipaeda specimens were collected.…”
Section: T Callipaeda Morphological Identificationmentioning
confidence: 99%